Effect of incorporation of remineralizing agents into bleaching gels on the microhardness of bovine enamel in situ - Borges, Alessandra Bühler [UNESP]; Guimarães, Carolina Anne [UNESP]; Bresciani, Eduardo [UNESP]; Ramos, Carolina Judica [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Torres, Carlos Rocha Gomes [UNESP] (Jaypee Brothers Medical Publishing, 2014)
This study evaluated the effect of adding calcium or fluoride to 35% hydrogen peroxide (HP) bleaching gel and the effect of human saliva on the microhardness of sound and demineralized enamel, using an in situ model. Cylindrical bovine enamel specimens (3 × 2 mm) were divided into two groups (n = 30): sound enamel (SE) and demineralized enamel (DE). Each group was divided into three subgroups, according to the bleaching gel: 35% HP; 35% HP + calcium; 35% HP + fluoride. After bleaching therapy, the specimens were fixed to intraoral devices worn by 10 volunteers for 7 days. Surface enamel microhardness (SMH) was measured before and after bleaching procedures, and after 1 and 7 days of saliva exposure. Data were analyzed by Repeated Measures ANOVA (5%). The variable time resulted in significant differences for SE and DE groups (p = 0.001). For SE, significantly lower SMH was detected for control at post-bleaching period in comparison to the baseline and after 7 days. For DE, the lowest mean values were obtained before bleaching, and the addition of calcium to the peroxide significantly increased enamel SMH. The exposure to human saliva resulted in increased SMH. The addition of potential remineralizing agents into bleaching gels might play an important role in maintaining the microhardness of sound enamel and in inducing remineralization of artificially demineralized enamel right after bleaching, and the remineralizing action of human saliva might minimize the deleterious effects of bleaching gels on enamel. Clinical significance: The incorporation of calcium into HP bleaching gel might be beneficial for the initial phases of the bleaching procedure.
Keywords: Fluoride; Calcium; Enamel; Hydrogen peroxide; Microhardness